Pengaruh Optimalisasi Bibit dan Pupuk Kandang Ayam Terhadap Pertumbuhan Vegetatif Tanaman Padi Intensifikasi SRI - Masdar Masdar; Musliar Kasim (Jurnal Agrista, 2009)
Influences of Seedling Optimizations and cock secretion fertilizer on rice plant vegetative growth in the system of rice intensification: SRIABSTRACT. The application or the system of rice intensifications (SRI), including seedling and optimalizations and cock secretion fertilizer (CSF) were done. The treatment aim to know the local production level in heavy wet tropic region. The research was conducted in Limau Manis, aside the campus of Andalas University, from July to December 2005 used var. Cisokan. The spilt plot design was applied in the research. The fertilizers were applied according to the recommended 200kg Urea, 200kg SP-36, 150kg KCl. The research variables are plant growth rate, net assimilation ratio, leaf area index, leaf area ratio, shoot/root ratio, tiller number, water use efficiency, and evaporating/ transpiration ratio. The research conclude that the higher the CSF input, the higher the plant vegetative growth. Besides, there were found no different response of 1 to 2 applied seedling, as well as 7 days to 14 days applied seedling with the input.